2019
DOI: 10.4162/nrp.2019.13.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenic obesity can be negatively associated with active physical activity and adequate intake of some nutrients in Korean elderly: Findings from the Korea National Health and Nutrition Examination Survey (2008–2011)

Abstract: BACKGROUND/OBJECTIVESThe aim of this study was to analyze the factors related to sarcopenic obesity among the elderly in South Korea.SUBJECTS/METHODSA total of 3,367 elderly (≥ 65 years) from the Korea National Health and Nutrition Examination Survey (2008–2011) were included in this analysis. The subjects were assessed to determine their sarcopenia and obesity status. Sarcopenia was assessed by determining their appendicular skeletal muscle mass (ASM). Obesity was defined by the waist circumference. An associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 46 publications
5
15
0
Order By: Relevance
“…It has also been reported that PA can increase walking speed, balance, and daily life activities in older people with sarcopenia ( Steffl et al, 2017 ), and that it can improve mobility and physical function in older patients ( Chou et al, 2012 ; De Vries et al, 2012 ). Son et al (2019) reported that the prevalence of sarcopenia, obesity, and sarcopenic obesity significantly decreased when over 2900 MET-min/week of PA was performed. In this study, moderate-active PA was effective in preventing sarcopenia, and few older adults with obesity and sarcopenic obesity in high-active PA, supporting the results of prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that PA can increase walking speed, balance, and daily life activities in older people with sarcopenia ( Steffl et al, 2017 ), and that it can improve mobility and physical function in older patients ( Chou et al, 2012 ; De Vries et al, 2012 ). Son et al (2019) reported that the prevalence of sarcopenia, obesity, and sarcopenic obesity significantly decreased when over 2900 MET-min/week of PA was performed. In this study, moderate-active PA was effective in preventing sarcopenia, and few older adults with obesity and sarcopenic obesity in high-active PA, supporting the results of prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, owing to decrease of outdoor physical activities, vitamin D produces less with scanty expose of ultraviolet radiation ( 19 ). Hence, inadequate vitamin D accelerates SO ( 20 ).…”
Section: Pathogenesis and Complications Of Sarcopenic Obesitymentioning
confidence: 99%
“…Thus, defining sarcopenic obesity only in terms of muscle mass is too narrow maybe of limited clinical value that becomes more common in people over the age of 65. Sarcopenic obesity factor seropositivity, and a lack of current treatment with disease-modifying anti-sarcopenic obesity drugs were significantly associated with abnormal body composition such as increasing joint deformity, disability scores and C-reactive protein levels [25]. After middle age, adults lose 3% of their muscle strength every year, on average, to perform many routine activities [26].…”
Section: Ketogenic Diet Is Good For Aging-related Sarcopenic Obesitymentioning
confidence: 99%